1994
DOI: 10.1002/tea.3660310207
|View full text |Cite
|
Sign up to set email alerts
|

The effect of levels of cooperation within physical science laboratory groups on physical science achievement

Abstract: The purpose of this study was to investigate the effect of the levels of group cooperation on students' achievement during a series of physical science laboratory activities. Six intact seventh-grade physical science classes taught by two teachers, with each teacher instructing three classes, were selected from two middle schools. For each teacher, one of the classes was taught with a traditional approach (no cooperative goal structure). The other two classes were assigned to a cooperative goal structure (role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1
6

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 42 publications
1
16
1
6
Order By: Relevance
“…For example, Chang and Lederman (1994) applied cooperative learning to investigate students' physical science achievement and found that cooperative learning had no significant difference on students' achievement. Similar findings were reported by Seymour (1994) and Tingle & Good (1990) as cited in Chang and Mao (1999).…”
Section: Cooperative Learning and Academic Achievementmentioning
confidence: 99%
“…For example, Chang and Lederman (1994) applied cooperative learning to investigate students' physical science achievement and found that cooperative learning had no significant difference on students' achievement. Similar findings were reported by Seymour (1994) and Tingle & Good (1990) as cited in Chang and Mao (1999).…”
Section: Cooperative Learning and Academic Achievementmentioning
confidence: 99%
“…Ebenezer and Zoller (1993) commented that students often fail to see the connection between the prepared laboratory activities and the content to be learned. Chang and Lederman (1994) and Tamir (1989) suggest that the teacher is the key to effective learning in the laboratory. Tamir also suggests that one reason for the failure of many science courses is the attempt to use laboratory work for aims for which it is ill suited, such as teaching theoretical concepts rather than process skills.…”
mentioning
confidence: 97%
“…There is a wide range of views about the significance of laboratory work with some educators believing that laboratory work has a central role in science teaching (Chang & Lederman, 1994;Ebenezer & Zoller, 1993) while others feel that too much emphasis on laboratory activities leads to a narrow conception of science (Hodson, 1992). In a study conducted in Tasmanian schools, Lynch and Ndyetabura (1982) argued that teachers' aims of practical work in schools are in some respects misguided or misjudged and, when viewed against student perceptions, there are some major mismatches.…”
mentioning
confidence: 99%
“…탐구적 과학 글쓰기 활동이 학생들의 개념학습, 사 고력, 과학적 소양의 함양, 학생들의 성취 수준의 격 차를 줄이는데 긍정적인 영향을 준다고 보고하였고 (Akkus et al, 2007;Keys et al, 1999;Hand et al, 2006;Prain, 2006), 국내에서도 탐구적 과학 글 쓰기 수업이 학생들의 과학개념 이해, 과학 탐구능력 및 과학적 태도 향상, 비판적 사고력 신장에 도움이 된다고 연구된 바 있다 (김미정, 2011; 남정희 등, 2008; 이은경, 강성주, 2006 (Hodson, 1990;Lunetta, 1998). 이러한 원인은 소집단의 일부 구성원이 주도 적으로 실험 활동을 함으로써 나머지 학생들은 방관 자적 입장에 놓이게 되며 (Basili & Sanford, 1991;Chang & Lederman, 1994), 또한 과학실험을 할 때 능력이 서로 다른 모둠에서 상위 수준의 학생은 논의 할 동료를 찾지 못하고, 하위 수준의 학생은 상위 수 준의 학생의 설명을 이해하지 못함으로써 모둠의 상 호작용은 점점 약화되고 (성숙경, 최병순, 2007), 동질 적 집단 구성이 성취도 및 태도에서 긍정적인 효과를 가져 온다 (Lawrenz & Munch, 1984) Write down subjects you would like to study as many as possible after reading reference regarding yellow dust.…”
Section: ⅰ 서 론unclassified